Planejamento curricular na Educação Profissional: análise da percepção dos professores do Senac São Paulo - Masmo, Patrícia Luissa (2024)
The problem that gave rise to this research is the disconnection between the theoretical and practical knowledge of the professional field and the theoretical-practical pedagogical knowledge in professional training. This thesis aims to investigate the influence of curriculum planning on the (effective) pedagogical action of teachers in professional education. The field investigated was Senac São Paulo from the perspective of its teachers in various units across the state. It is a mixed-method project of a qualiquantitative nature with integrated and simultaneous data collection and analysis strategies (CRESWELL, 2010). The research is structured based on Grounded Theory foundations (CHARMAZ, 2012), with the Paradigm of Complexity (MORIN, 2006) as the theoretical-methodological reference. To describe the practices, the processes and services of curriculum planning at Senac São Paulo were mapped, and for the research description, critical approaches to curriculum (CASALI, 2018) and planning in professional education were identified. Teachers' perceptions were analyzed, and conditions such as participation in institutional curriculum planning, teaching experience, and specific higher education were examined in depth. The procedures adopted for data collection were as follows: (1) Systematic Literature Review on Planning and Curriculum, especially those adopting multi-referential (ARDOINO, 1998) and intercultural (CANDAU, 2016) approaches in Professional Education, and (2) field research, using a questionnaire combining closed-ended (Likert scale) and open-ended questions. The questionnaire was validated by judges and a pre-test. Information was collected, organized, and categorized using SurveyMonkey, Excel, SPSS, and NVivo. Quantitative data were analyzed using Descriptive Statistics and the chi-squared test for variable associations. Qualitative data were coded (CHARMAZ, 2012) and subsequently analyzed in an integrated manner using quantitative data. The results of this research demonstrate that teachers are actively engaged, displaying an awareness of the complex dynamics involved in comprehensive professional education. We have identified perspectives that directly influence practice, leading to the proposal of a model that emphasizes the interconnection and mutual influence of curriculum-planning elements. The goal is to promote cohesion, establish connections between professional and pedagogical domains, and encourage autonomy and flexibility for contextualized adaptations